2020
DOI: 10.3390/molecules25143225
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of Au/Disentangled UHMWPE: A Combined Optical and Structural Study

Abstract: The term disentangled refers to polymers with fewer entanglements in the amorphous regions, a metastable condition that can significantly affect the material’s properties and processing behavior. The lower entanglement density in ultra-high molecular weight polyethylene (dis-UHMWPE) facilitates the solid-state processability into uniaxially-oriented specimens reaching very high draw ratios and crystallinities. In this study, Au/dis-UHMWPE nanocomposites were formulated and processed at variable draw ratios. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…In both images, highly oriented fibers extending over tens of microns are visible. Since PE is transparent to visible light, Au nanoparticles (diameter: ∼ 2 − 12 nm [58]; concentration: 1 wt%) were added as an optical absorber. The concentration of the Au was selected to minimize the effect of the filler on the thermal conductivity while enabling the formation of a thermal grating on the sample [57].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both images, highly oriented fibers extending over tens of microns are visible. Since PE is transparent to visible light, Au nanoparticles (diameter: ∼ 2 − 12 nm [58]; concentration: 1 wt%) were added as an optical absorber. The concentration of the Au was selected to minimize the effect of the filler on the thermal conductivity while enabling the formation of a thermal grating on the sample [57].…”
Section: Methodsmentioning
confidence: 99%
“…Experimental characterization of similar samples using polarized light microscopy, among other methods, indicates that the nanoparticles are oriented in linear chains in the amorphous regions. [58] A representative TG signal measured at grating period L = 9.8 µm is shown in Fig. 1…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] UHMWPE fibers are of great importance to mankind because of their increasing demand in fields ranging from civil materials to basic materials for military aviation depending on their simple structure, low density, outstanding tensile property, excellent wear resistance and other properties. [4][5][6][7][8] The methods for preparing UHMWPE fibers mainly include solid-phase extrusion method, 9,10 surface crystal growth method, 11 plasticized melt-spinning method 12,13 and gelspinning-hot-drawing method 14,15 and so forth. But compared with other preparation methods, the gel-spinninghot-drawing method has many merits, such as excellent properties of prepared fibers, easy control of spinning process and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, an amorphous network phase was created by the interactions among local molecular chains with physical cross-linkage in the disordered molecular regions (Deplancke et al , 2019; Tang et al , 2019). Drakopoulos (2020) revealed that molecular chains with fewer entanglements in the amorphous regions can significantly affect the material’s properties and processing behaviors. Chen (2018) found that the amorphous regions were prone to be damaged by external factors, and the segments with low molecular weights were the result of chain scission and chain oxidation, leading to higher crystallinity.…”
Section: Introductionmentioning
confidence: 99%